Two adult females with a distinct familial mental retardation syndrome: non-progressive neurological symptoms with ataxia and hypotonia, similar facial appearance, hypergonadotrophic hypogonadism, and retinal dystrophy. Issue 4 (April 1998) - Fryns, J P; Van Lingen, C; Devriendt, K; Legius, E; Raus, P
Abstract : We describe a familial mental retardation syndrome in a 30 year old, moderately mentally retarded female and her 59 year old maternal aunt. Both presented the distinct association of (1) a non-progressive neurological syndrome with ataxia and hypotonia, (2) similar craniofacial appearance with a narrow forehead, prominent supraorbital ridges and tendency to synophrys, deeply set eyes with short, upward slanting palpebral fissures, short philtrum, and large mouth, (3) hypergonadotrophic hypogonadism, and (4) retinal dystrophy with onset in early adulthood.